Comparison of submucosal tunneling biopsy versus EUS-guided FNA for gastric subepithelial lesions: a prospective study with crossover design - Kobara, Hideki; Mori, Hirohito; Nishimoto, Naoki; Fujihara, Shintaro; Nishiyama, Noriko; Ayaki, Maki; Yachida, Tatsuo; Matsunaga, Tae; Chiyo, Taiga; Kobayashi, Nobuya; Fujita, Koji; Kato, Kiyohito; Kamada, Hideki; Oryu, Makoto; Tsutsui, Kunihiko; Iwama, Hisakazu; Haba, Reiji; Masaki, Tsutomu (Endoscopy International Open, 2017)
Background and study aims Endoscopic ultrasound-guided fine needle aspiration (FNA) for gastrointestinal subepithelial lesions (SELs) has limited diagnostic accuracy due to technical problems and small lesion size. We previously reported a novel submucosal tunneling biopsy (STB) technique for sampling SELs. This study aimed to evaluate the diagnostic ability and safety of STB compared to that of FNA for SELs.Patients and methods The study was a non-randomized, prospective comparative study with crossover design in patients with endoluminal gastric SELs. Forty-three patients, including 29 cases with lesions < 2 cm were enrolled. A crossover design with 2 intervention stages (Group A: FNA followed by STB for 23 SELs, Group B: STB followed by FNA for 20 SELs) was implemented. The primary outcome was the diagnostic yield (DY). Secondary outcomes were technical success rate, procedure time, complication rate, and sample quality.Results The DY of STB was significantly higher than that of FNA (100 % vs. 34.8 %; P < 0.0001) in group A, including 100 % in overall STB. The technical success rate of STB was significantly higher than that of FNA (100 % vs. 56.5 %; P = 0.0006), whereas the median procedure time of STB was significantly longer than that of FNA (37 minutes vs. 18 minutes; P < 0.0001). The median specimen area of STB samples was markedly larger than that of FNA samples (5.54 mm2 vs. 0.69 mm2; P < 0.001). No complications occurred in either method.Conclusions STB had significantly superior diagnostic ability and a more adequate sample quality than FNA for endoluminal gastric SELs, indicating the suitability of STB for small SELs.Clinical trial registration: UMIN 000006754